The effect high-intensity short-term heat acclimation on physiological and perceptual response to exercise in the heat in trained cyclists - Tyler, C. J.; Teles, F.; Chianca, M.; Gordon, R.; Laursen, P. B.; Lee, J. K. W.; Reeve, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Short (< 7 days), prolonged (~ 60 min), submaximal heat acclimation regimens have been shown to induce physiological adaptations to heat exposure (Chalmers et al., 2014); however, pre-competition tapering traditionally involves periods of low volume, high-intensity training. The aim of the present study was to establish the effect of a high-intensity short-term heat acclimation (HISTHA) on heat adaptation parameters in trained cyclists. Methods: Thirteen trained male cyclists (37 ± 11 y; 184 ± 8 cm; 84 ± 8 kg; 60 ± 9 ml/kg/min; 328 ± 37 Wmax) undertook 5 consecutive days of HISTHA. Each day involved a 6 min warm-up followed by ~12 x 1-min sprints at 100% Wmax separated by 1-min active rest, in the heat (35°C; 50% rh). Rectal temperature (Tr), heart rate (HR), power output (W), weighted-mean skin temperature (Tsk), rating of perceived exertion (RPE), thermal sensation (TS), sweat rate, haematological data, and ad libitum fluid consumption were recorded throughout. Effect sizes (g or r) were calculated from mean and standard deviations, or z scores and sample sizes, as appropriate. Results: There was no difference between day 1 and day 5 for the total work completed (332 ± 45 vs. 334 ± 39 W; g= 0.05). Thermal impulse was lower on day 5 (0.06 ± 0.01 vs. 0.05 ± 0.01°C/hr; g = -0.97). When comparing day 1 with day 5, there was a small increase in Tr-rest (36.8 ± 0.5 vs. 37.0 ± 0.3°C; g = 0.47), Tr-mean (37.4 ± 0.3 vs. 37.5 ± 0.2°C; g = 0.38) and total voluntary fluid consumption (1.4 ± 0.6 vs. 1.6 ± 0.8 l/hr; g = 0.27). There were small reductions in HRmean (149 ± 16 vs. 143 ± 13 b/min; g < -0.40) and RPEmedian (16 (13-19) vs. 16 (13-19); r = -0.22), moderate reductions in TSmedian (7 (5-8) vs. 7 (5-8); r = 0.65), and large reductions in Tsk-mean and Tsk-peak (mean: 35.4 ± 0.5 vs. 35.1 ± 0.3°C; g = -0.70; peak: 36.4 ± 0.6 vs. 35.9 ± 0.4°C; g = -0.95). There was no effect on Tr-peak (38.1 ± 0.3 vs. 38.1 ± 0.3°C; g < 0.01), HRrest (73 ± 15 vs. 73 ± 14 b/min; g < 0.01), Tsk-rest (33.9 ± 0.8 vs. 33.8 ± 0.6°C; g = -0.14), resting plasma volume (64 ± 6 vs. 63 ± 6 %; g = -0.15) or sweat rate (2.7 ± 1.1 vs. 2.6 ± 0.7 l/hr; g = -0.11). Conclusion: A 5 day, 30-min HISTHA regimen improved HR, Tsk, and perceptual responses during exercise in the heat, but had no effect on plasma volume. The degree of change in thermoregulatory and cardiovascular variables was less than that typically shown with more prolonged low intensity heat acclimation protocols.